Pd-based alloy catalyst for hydrogen production from formic acid and preparation method of Pd-based alloy catalyst
By using histidine, PD front -drive, and metal salt to prepare PD conformal alloy alloy nanoparticles and load them to the carbon carrier, the problem of low catalytic efficiency, high cost and stability in hydrogen hydrogen in hydrogen in methic acid have been solved. High -efficiency, low -cost hydrogen -making effect.
Patent Information
- Application Number
- CN202411450667.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-17
- Publication Date
- 2025-01-21
AI Technical Summary
The existing catalysts used for hydrogen production of formic acid have problems such as low catalytic efficiency, high cost and stability that need to be improved in large-scale industrial applications.
Use the histidine, PD pre -drive body, and metal salt as raw materials to prepare neutrons, and restore it as a PD base alloy nano particles through a reducing agent, and load them to the carbon carrier to prepare an efficient PD karm alloy catalyst.
The PD -alloy catalyst shows excellent electrical catalytic activity and stability during hydrogen acid hydrogen, has high hydrogen analysis efficiency and low economic costs, and is suitable for industrialized applications.
Smart Images

Figure CN119327448A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of hydrogen production from formic acid, and particularly relates to a Pd-based alloy catalyst for hydrogen production from formic acid and a preparation method thereof. Background Art
[0002] Compared with fossil energy, hydrogen, as an ideal clean energy, has the advantages of high energy density, green environmental protection, and recyclability. However, the flammability and low density of hydrogen make it difficult to transport and pose safety risks. In contrast, formic acid has the advantages of high mass / volume hydrogen capacity, high density, liquid form, and no biological toxicity. It is widely available and has mild dehydrogenation conditions. It is a chemical hydrogen storage material with broad application prospects.
[0003] In recent years, the technology of hydrogen production from formic acid has been continuously developing, but its core challenge is still to develop high-performance and low-cost dehydrogenation catalysts to meet the needs of large-scale industrial applications. At present, the catalysts used for hydrogen production from formic acid are mainly divided into homogeneous catalysts and heterogeneous catalysts. Although homogeneous catalysts have excellent catalytic activity, their hydrogen production conditions are complex, and separation and recovery are difficult, which limits the feasibility of their large-scale application. These shortcomings are effectively solved in heterogeneous catalysts. However, heterogeneous catalysts still face problems such as low catalytic efficiency, high cost, and catalyst stability needs to be further improved. Therefore, the key to the large-scale application of formic acid hydrogen production lies in the development of efficient and low-cost catalysts. Summary of the invention
[0004] In view of the technical problems existing in the background technology, the purpose of the present invention is to provide a Pd-based alloy catalyst for hydrogen production from formic acid and a preparation method thereof. The Pd-based alloy catalyst exhibits excellent electrocatalytic activity and stability when used in hydrogen production from formic acid.
[0005] In order to achieve the above object, the present invention adopts the following technical solutions:
[0006] A first aspect of the present invention provides a method for preparing a Pd-based alloy catalyst for producing hydrogen from formic acid, comprising the following steps:
[0007] The complex is prepared using histidine, a Pd precursor and a metal salt as raw materials;
[0008] The prepared complex is reduced to Pd-based alloy nanoparticles using a reducing agent and loaded onto a carbon support to obtain a Pd-based alloy catalyst.
[0009] Preferably, the method specifically comprises the following steps:
[0010] S11, ultrasonically dispersing the carbon carrier into deionized water to obtain a carbon carrier suspension;
[0011] S12, adding the Pd precursor and the metal salt to the histidine solution, mixing evenly, to obtain a mixed solution A;
[0012] S13, adding the mixed solution A to the carbon support suspension, stirring for reaction, and obtaining a complex solution;
[0013] S14, adding the reducing agent solution into the complex solution, stirring for reaction, and purifying to obtain a Pd-based alloy catalyst.
[0014] Preferably, in step S11, the carbon carrier and deionized water are used in a ratio of 0.1-0.5 g: 5-20 ml; and the ultrasonic time is 30-60 min.
[0015] Preferably, in step S12, the molar ratio of the Pd precursor to histidine is 1:1-4, the molar ratio of the Pd precursor to the metal salt is 1:1-2; and the ratio of the reducing agent to the Pd content in the Pd precursor is 5-10:1.
[0016] Preferably, in step S13, the stirring reaction temperature is room temperature, the concentration of the reducing agent solution is 0.5-1 mol / L, the stirring reaction time is 30-60 min, and the stirring speed is 400-700 rpm.
[0017] Preferably, in step S14, the purification includes: washing, centrifuging and drying the reaction product, the centrifugal speed is 8000-10000 r / min, the drying temperature is 40-80° C., and the drying time is 12-18 h.
[0018] Preferably, the Pd precursor is one of Na2PdCl4, Pd(NO3)2, K2PdCl4, or a combination of two or more thereof.
[0019] Preferably, the metal salt is a soluble transition metal salt or a noble metal salt, more preferably a soluble metal salt of a metal such as Ag, Au, Cu, Ni, Zn or Co, such as silver nitrate, HAuCl4, etc.
[0020] Preferably, the carbon carrier is any one of XC-72R carbon black, commercial mesoporous carbon, carbon nanotubes, C3N4, and graphene oxide; and the reducing agent is NaBH4.
[0021] The second aspect of the present invention provides the use of the above-mentioned Pd-based alloy catalyst in hydrogen production from formic acid, and the specific formic acid hydrogen production comprises the following steps:
[0022] The formic acid-containing raw material and the Pd-based alloy catalyst prepared by the above method are placed in a reactor, stirred, and dehydrogenation reaction is carried out to recover the product.
[0023] Preferably, the temperature of the dehydrogenation reaction is 25-80°C, and the stirring speed is 100-350rpm;
[0024] Preferably, the formic acid-containing raw material is a mixture of formic acid and sodium formate, and the molar ratio of formic acid to sodium formate in the mixture is 1:1-4; the concentration of the formic acid is 0.5-3 mol / L.
[0025] Preferably, the amount of the Pd-based alloy catalyst is 0.05-0.5 g, and the molar ratio of Pd metal to formic acid in the Pd-based alloy catalyst is 1:50-200.
[0026] Preferably, the temperature of the dehydrogenation reaction is 25-80° C., and the stirring speed is 100-350 rpm.
[0027] Preferably, the recovered product is a mixed gas of hydrogen and carbon dioxide.
[0028] The present invention has the following beneficial effects:
[0029] (1) The present invention uses histidine, a Pd precursor and a metal salt as raw materials to prepare a complex, and then uses a reducing agent to reduce the complex to Pd-based alloy nanoparticles and loads them on a carbon carrier, thereby preparing a Pd-based alloy catalyst. When the Pd-based alloy catalyst is used for hydrogen production from formic acid, it exhibits excellent catalytic activity and has the advantages of high hydrogen evolution efficiency and low economic cost.
[0030] (2) The preparation method of the present invention is simple to operate, the carrier cost is low and the source is wide, and the yield is high, which meets the requirements of practical application and is suitable for industrial promotion. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0032] Figure 1 This is the TEM image of PdAg-His-CB-1 prepared in Example 1. DETAILED DESCRIPTION
[0033] In the following description, for the purpose of illustration rather than limitation, specific details such as specific system structures and technologies are provided to provide a thorough understanding of the embodiments of the present invention. However, it should be clear to those skilled in the art that the present invention may also be implemented in other embodiments without these specific details.
[0034] Example 1
[0035] A method for preparing a Pd-based alloy catalyst for producing hydrogen from formic acid, comprising the following steps:
[0036] (1) Take 0.1 g of XC-72R carbon black and add it to 5 ml of deionized water, shake it with ultrasonic for 30 min, and mix it thoroughly to obtain a carbon black suspension;
[0037] (2) 0.05 g of histidine and 0.018 g of Na2PdCl4 were added to 20 ml of deionized water, and then 0.6 ml (1 mol / L) of silver nitrate solution was added and mixed well to obtain a mixed solution A;
[0038] (3) Add the mixed solution A to the above carbon black suspension, stir at 800 rpm for 30 min to obtain a complex, then slowly drop 1 ml (0.5 mol / L) NaBH4 solution into the complex, and stir to react for 30 min;
[0039] (4) After the reaction, the solid product was separated by centrifugation at a speed of 10000 r / min for 5 min. The solid product was washed with deionized water for 3 times and then dried at 60° C. under vacuum conditions for 12 h to obtain a Pd-based alloy catalyst, which was recorded as PdAg-His-CB-1.
[0040] Example 2
[0041] A method for preparing a Pd-based alloy catalyst for producing hydrogen from formic acid, comprising the following steps:
[0042] (1) 0.1 g of XC-72R carbon black was added to 5 ml of ultrapure water and ultrasonically vibrated for 30 min to fully mix to obtain a mesoporous carbon suspension;
[0043] (2) 0.1 g of histidine and 0.018 g of Na2PdCl4 were added to 20 ml of deionized water, and then 0.6 ml (1 mol / L) of silver nitrate was added and mixed well to obtain a mixed solution A;
[0044] (3) Add the mixed solution A to the above mesoporous carbon suspension, stir at 800 rpm for 20-30 min to obtain a complex, slowly drop 1 ml (0.5 mol / L) NaBH4 solution into the complex, and stir for 30 min;
[0045] (4) After the reaction is completed, the solid product is separated by centrifugation at a speed of 10000 r / min for 5 minutes. The solid product is washed with deionized water for 3 times and then dried at 60° C. under vacuum conditions for 12 hours to obtain a Pd-based alloy catalyst, which is recorded as PdAg-His-CB-2.
[0046] Example 3
[0047] A method for preparing a Pd-based alloy catalyst for producing hydrogen from formic acid, comprising the following steps:
[0048] (1) Take 0.1 g of XC-72R carbon black and add it to 5 ml of ultrapure water, shake it with ultrasonic for 30 min, and mix it thoroughly to obtain a carbon black suspension;
[0049] (2) 0.025 g of histidine and 0.018 g of Na2PdCl4 were added to 20 ml of deionized water, and then 0.6 ml (1 mol / L) of silver nitrate solution was added and mixed well to obtain a mixed solution A;
[0050] (3) Add the mixed solution A to the above carbon black suspension, stir at 800 rpm for 20-30 min to obtain a complex, slowly drop 1.5 ml (1 mol / L) NaBH4 solution into the complex, and stir to react for 30 min;
[0051] (4) After the reaction is completed, the solid product is separated by centrifugation at a speed of 10000 r / min for 5 minutes. The solid product is washed with deionized water for 3 times and then dried at 60° C. under vacuum conditions for 12 hours to obtain a Pd-based alloy catalyst, which is recorded as PdAg-His-CB-3.
[0052] Example 4
[0053] A method for preparing a Pd-based alloy catalyst for producing hydrogen from formic acid, comprising the following steps:
[0054] (1) Take 0.1 g of XC-72R carbon black and add it to 5 ml of ultrapure water, shake it with ultrasonic for 30 min, and mix it thoroughly to obtain a carbon black suspension;
[0055] (2) 0.05 g of histidine and 0.018 g of Pd(NO3)2 were added to 20 ml of deionized water, and then 0.6 ml (1 mol / L) of silver nitrate solution was added and mixed well to obtain a mixed solution A;
[0056] (3) Add the mixed solution A to the above carbon black suspension, stir at 800 rpm for 20-30 min to obtain a complex, slowly drop 1.5 ml (1 mol / L) NaBH4 solution into the complex, and stir to react for 30 min;
[0057] (4) After the reaction is completed, the solid product is separated by centrifugation at a speed of 10000 r / min for 5 minutes. The solid product is washed with deionized water for 3 times and then dried at 40° C. under vacuum conditions for 18 hours to obtain a Pd-based alloy catalyst, which is recorded as PdAg-His-CB-4.
[0058] Example 5
[0059] A method for preparing a Pd-based alloy catalyst for producing hydrogen from formic acid, comprising the following steps:
[0060] (1) Take 0.1 g of XC-72R carbon black and add it to 5 ml of ultrapure water, shake it with ultrasonic for 30 min, and mix it thoroughly to obtain a carbon black suspension;
[0061] (2) 0.05 g of histidine and 0.018 g of Na2PdCl4 were added to 20 ml of deionized water, and then 0.021 g of HAuCl4 was added and mixed well to obtain a mixed solution A;
[0062] (3) Add the mixed solution A to the above carbon black suspension, stir at 800 rpm for 25 min to obtain a complex, slowly drop 1.5 ml (1 mol / L) NaBH4 solution into the complex, and stir to react for 30 min;
[0063] (4) After the reaction is completed, the solid product is separated by centrifugation at a speed of 10000 r / min for 5 min. The solid product is washed three times with deionized water and then dried at 60° C. under vacuum conditions for 12 h to obtain a Pd-based alloy catalyst, which is recorded as PdAu-His-CB.
[0064] Comparative Example 1
[0065] The method is basically the same as Example 1, except that histidine is not added, and a Pd-based alloy catalyst is obtained, which is recorded as PdAg-CB.
[0066] Comparative Example 2
[0067] The method is basically the same as Example 1, except that no silver nitrate solution is added, and a Pd-based catalyst is obtained, which is recorded as Pd-His-CB.
[0068] Comparative Example 3
[0069] The method is basically the same as Example 1, except that "XC-72R carbon black" is replaced by "commercial mesoporous carbon" to obtain a Pd-based alloy catalyst, which is recorded as PdAg-His-MSC.
[0070] The Pd-based alloy catalyst prepared in Example 1, specifically PdAg-His-CB-1, was characterized by TEM. Figure 1 shown.
[0071] Depend on Figure 1 The results show that in the Pd-based alloy catalyst prepared in Example 1, the PdAg alloy nanoparticles are uniformly loaded on the surface of the carbon black carrier.
[0072] Test Example 1
[0073] 0.1 g of the Pd-based alloy catalyst prepared in Example 1, specifically PdAg-His-CB-1, and 5 mL of deionized water were weighed and added to a three-necked flask, and the flask was placed in an oil bath (60° C., 200 rpm) for stirring, and a gas collection device was connected and the air tightness was checked; then, 1 ml of a mixed solution of 3 mol / L formic acid and 3 mol / L sodium formate was quickly injected and the timing was started, and the gas volume was recorded, and the gas composition was qualitatively and quantitatively analyzed using a gas chromatograph. The results are shown in Table 1.
[0074] Test Example 2
[0075] The experiment was basically the same as that in Experiment 1, except that the concentration of the sodium formate solution was replaced from "3 mol / L" to "6 mol / L". The results are shown in Table 1.
[0076] Test Example 3
[0077] The experiment was basically the same as that in Experiment 1, except that the concentration of the sodium formate solution was replaced from "3 mol / L" to "9 mol / L". The results are shown in Table 1.
[0078] Test Example 4
[0079] It is basically the same as Experimental Example 1, except that "PdAg-His-CB prepared in Example 1" is replaced by "PdAu-his-CB prepared in Example 5". The results are shown in Table 1.
[0080] Test Example 5
[0081] It is basically the same as Experimental Example 1, except that "PdAg-His-CB-1 prepared in Example 1" is replaced by "PdAg-CB prepared in Comparative Example 1". The results are shown in Table 1.
[0082] Test Example 6
[0083] It is basically the same as Experimental Example 1, except that "PdAg-His-CB-1 prepared in Example 1" is replaced by "Pd-His-CB prepared in Comparative Example 2". The results are shown in Table 1.
[0084] Test Example 7
[0085] It is basically the same as Experimental Example 1, except that "PdAg-His-CB prepared in Example 1" is replaced by "PdAg-His-MSC prepared in Comparative Example 3". The results are shown in Table 1.
[0086] Test Example 8
[0087] It is basically the same as Experimental Example 1, except that "PdAg-His-CB-1 prepared in Example 1" is replaced by "PdAg-His-CB-2 prepared in Example 2". The results are shown in Table 1.
[0088] Test Example 9
[0089] It is basically the same as Experimental Example 1, except that "PdAg-His-CB-1 prepared in Example 1" is replaced by "PdAg-His-CB-3 prepared in Comparative Example 3". The results are shown in Table 1.
[0090] Table 1
[0091]
[0092] As shown in Table 1, the Pd-based alloy catalyst prepared by the present invention exhibits excellent electrocatalytic activity when applied to formic acid hydrogen production, especially when loaded with PdAu alloy, the obtained PdAu-His-CB exhibits the best formic acid hydrogen production effect; the test results of comparative test examples 1-3 show that the addition of sodium formate in the raw material during formic acid hydrogen production has a certain promoting effect on formic acid dehydrogenation, and the higher the sodium formate concentration, the higher the dehydrogenation efficiency. In addition, the test results of comparative test examples 1, 5, 8 and 9 show that this is because the added histidine forms a complex with the metal palladium ion, which regulates the growth and nucleation of the metal palladium on the carrier, thereby promoting the dispersion of PdAg on the carrier, and significantly improving the activity of the catalyst; in addition, the amino group in the histidine provides a basic site, which further promotes the process of formic acid deprotonation, so that the prepared Pd-based alloy catalyst exhibits excellent performance in formic acid decomposition and hydrogen production. Comparing the experimental results of Experimental Examples 1 and 7, compared with commercial mesoporous carbon, carbon black has higher conductivity, can effectively promote the transfer of electrons, and has stronger surface adsorption capacity, can adsorb more reactants, and thus exhibits better catalytic activity. Comparing the results of Experiments 1 and 6, it can be seen that the addition of the second metal forms a nano-alloy catalyst, promotes the mutual transfer of electrons between the two metals, changes the electronic structure of Pd, and thus improves the catalytic activity.
[0093] The present invention is not limited to the above-mentioned specific implementation modes. Various changes made by ordinary technicians in this field based on the above-mentioned concepts without creative work are all within the protection scope of the present invention.
Claims
1. A method for preparing a Pd-based alloy catalyst for producing hydrogen from formic acid, characterized in that: The following steps are involved: The complex is prepared using histidine, a Pd precursor and a metal salt as raw materials; The prepared complex is reduced to Pd-based alloy nanoparticles using a reducing agent and loaded onto a carbon support to obtain a Pd-based alloy catalyst.
2. The method for preparing a Pd-based alloy catalyst according to claim 1, characterized in that: The specific steps include: S11, ultrasonically dispersing the carbon carrier into deionized water to obtain a carbon carrier suspension; S12, adding the Pd precursor and the metal salt to the histidine solution, mixing evenly, to obtain a mixed solution A; S13, adding the mixed solution A to the carbon support suspension, stirring for reaction, and obtaining a complex solution; S14, adding the reducing agent solution into the complex solution, stirring for reaction, and purifying to obtain a Pd-based alloy catalyst.
3. The method for preparing a Pd-based alloy catalyst according to claim 2, characterized in that: In step S11, the carbon carrier and deionized water are used in a ratio of 1-5 g: 5-20 ml; and the ultrasonic time is 30-60 min.
4. The method for preparing a Pd-based alloy catalyst according to claim 2, characterized in that: In step S12, the molar ratio of the metal salt to histidine is 1:1-4, and the molar ratio of the Pd precursor to the metal salt is 1:1-2.
5. The method for preparing a Pd-based alloy catalyst according to claim 2, characterized in that: In step S13, the stirring reaction temperature is room temperature, the concentration of the reducing agent solution is 0.5-1 mol / L, the stirring reaction time is 30-60 min, and the stirring speed is 400-700 rpm; In step S14, the purification includes: washing, centrifuging and drying the reaction product, the centrifugal speed is 8000-10000 r / min, the drying temperature is 40-80° C., and the drying time is 12-18 h.
6. The method for preparing a Pd-based alloy catalyst according to claim 1, characterized in that: The Pd precursor is one of Na2PdCl4, Pd(NO3)2, K2PdCl4 or a combination of two or more thereof; the metal salt is a soluble metal salt of Ag, Au, Cu, Ni, Zn or Co; the carbon carrier is any one of XC-72R carbon black, carbon nanotubes, C3N4, and graphene oxide; and the reducing agent is NaBH4.
7. A Pd-based alloy catalyst prepared by the preparation method according to any one of claims 1 to 6.
8. Use of the Pd-based alloy catalyst as claimed in claim 7 in hydrogen production from formic acid.
9. The use according to claim 8, characterized in that: The specific steps of producing hydrogen from formic acid are: placing a formic acid-containing raw material and a Pd-based alloy catalyst in a reactor, stirring, performing a dehydrogenation reaction, and recovering the product.
10. The use according to claim 9, characterized in that: The formic acid-containing raw material is a mixture of formic acid and sodium formate, and the molar ratio of formic acid to sodium formate in the mixture is 1:1-4; the concentration of the formic acid is 0.5-3 mol / L; The amount of the Pd-based alloy catalyst is 0.05-0.5 g, and the molar ratio of Pd metal to formic acid in the Pd-based alloy catalyst is 1:50-200; The temperature of the dehydrogenation reaction is 25-80°C, and the stirring speed is 100-350rpm. The recovered product is a mixed gas of hydrogen and carbon dioxide.